Local dispersal pathways during the invasion of the cactus moth, Cactoblastis cactorum, within North America and the Caribbean - Andraca Gómez, Guadalupe (2020)
Cactoblastis cactorum, a species of moth native to Argentina, feeds on several prickly pear cactus species (Opuntia) and has been successfully used as a biological control of invading Opuntia species in Australia, South Africa and native ruderal Opuntia species in some Caribbean islands. Since its introduction to the Caribbean its spread was uncontrolled, invading successfully Florida, Texas and Louisiana. Despite this long history of invasion, we are still far from understanding the factors determining the patterns of invasion of Cactoblastis in North America. Here, we explored three non-mutually exclusive explanations: a) a stepping stone model of colonization, b) long distance colonization due to hurricanes, and/or c) hitchhiking through previously reported commercial routes. Genetic diversity, genetic structure and the patterns of migration among populations were obtained by analyzing 10 nuclear microsatellite loci. Results revealed the presence of genetic structure among populations of C. cactorum in the invaded region and suggest that both marine commercial trade between the Caribbean islands and continental USA, as well as recurrent transport by hurricanes, explain the observed patterns of colonization. Provided that sanitary regulations avoiding humanmediated dispersal are enforced, hurricanes probably represent the most important agent of dispersal and future invasion to continental areas.